2023
DOI: 10.1097/js9.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the surgical treatment of sacrococcygeal pilonidal sinus: a review

Abstract: Background: A pilonidal sinus (PS) is an acquired disease resulting from recurrent infections and chronic inflammation. A PS involving the sacrococcyx is referred to as a sacrococcygeal PS (SPS). An SPS is a rare chronic infectious disease for which surgery is a good choice. The incidence of SPS has gradually increased worldwide in recent years. However, surgeons have not reached a consensus on the preferred surgical approach for SPS. The authors performed a systematic review and meta-analysis to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 122 publications
0
13
0
Order By: Relevance
“…However, their relapse rate is higher. In the case of primary closure of the resulting defect (when minimally invasive treatment is not suitable), this must be done away from the midline, as the two most commonly used reconstructive techniques offer-the Limberg flap and the Karydakis procedure (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…However, their relapse rate is higher. In the case of primary closure of the resulting defect (when minimally invasive treatment is not suitable), this must be done away from the midline, as the two most commonly used reconstructive techniques offer-the Limberg flap and the Karydakis procedure (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…We have read the review on the progress in the surgical treatment of sacrococcygeal pilonidal sinus (SPS) 1 . The subject of the manuscript is interesting and topical.…”
mentioning
confidence: 99%
“…The authors evaluated 54 studies and included 3612 patients in their meta-analysis. The review of the medical literature was rigorously conducted 1 . The authors concluded that the midline closure technique has a much higher incidence of postoperative recurrence and infection than other techniques.…”
mentioning
confidence: 99%
See 2 more Smart Citations